Academic Integrity: Effects of Demographic Variables on Students’ Conduct - Soroya, Dr Muhammad Shahid; Hashmi, Dr Muhammad Amir; Soroya, Saira Hanif (South Asian Studies, 2020)
This study aimed to find out the effects of demographic variable i.e. gender, age, group of studies, GPA etc. on level of academic integrity among Pakistani students. The design of the study is quantitative in nature, in which the survey research method was employed to gather data from the respondents. A self-reported questionnaire was adapted on the basis of previously developed and validated questionnaire, with the consent of the authors. The developed scale was validated with the help of experts and pilot tested. Multilevel stratified convenience sampling technique was used to collect data from 4 provinces and federal area of Pakistan. The collected data was analyzed by using SPSS 16.0 version
Number: 2
Keywords: dept.ils